Input-dependent wave propagations in asymmetric cellular automata: Possible behaviors of feed-forward loop in biological reaction network - Akinori Awazu (Mathematical Biosciences and Engineering)
Dynamical aspects of the asymmetric cellular automata were in-vestigated to consider the signaling processes in biological systems. As a meta-model of the cascade of feed-forward loop type network motifs in biologicalreaction networks, we consider the one dimensional asymmetric cellular au-tomata where the state of each cell is controlled by a trio of cells, the cell itself,the nearest upstream cell and the next nearest upstream cell. Through thesystematic simulations, some novel input-dependent wave propagations werefound in certain asymmetric CA, which may be useful for the signaling pro-cesses like the distinction, the filtering and the memory of external stimuli.